Ex-military strategic leaders and corporate social performance: effects and boundaries - Ge Ren; Ping Zeng; Xi Zhong (European Research on Management and Business Economics, 2025)
Exmilitary strategic leaders, by whether and when they affect corporate social performance (CSP), have not been systematically explored to date. On the basis of imprinting theory, upper echelons theory, and empirical data from Chinese listed firms from 2011 to 2020, we obtain the following findings: (1) Exmilitary strategic leaders have a positive effect on firms’ CSP. (2) From the perspective of managerial discretion, industry discretion (e.g., industry turbulence) and institutional discretion (e.g., regional marketization) enhance the positive effect of ex-military strategic leaders on firms’ CSP. (3) From the perspective of firm characteristics, the positive effect of ex-military strategic leaders on firms’ CSP is more pronounced in state-owned and heavily polluting firms. (4) Social responsibility attention is a potential mechanism for ex-military strategic leaders and CSP. We contribute to the literature on strategic leaders and CSP by validating the influence of ex-military strategic leaders on firms’ CSP.